Lithuanian Associations in 1906–1915: Relations Between Associations and Authorities in Vilnius, Kaunas and Suwałki Governorates - Butkus, Martynas (History / Istorija, 2024)
Abstract. The article presents the legal regulation of associations in the Lithuanian governorates of the Russian Empire after the adoption of the Temporary Rules on Societies and Unions of 4 March 1906 and the relations of Lithuanian associations with the tsarist administration. It analyses the policies and attitudes of the local governors towards associations and how they relate to national and ideological issues. Despite the obstacles that Lithuanian associations faced from the authorities, the number of organisations in Lithuania grew rapidly between 1906 and 1915. The whole period had significant consequences for the development of Lithuanian civil society.